2010
DOI: 10.1016/j.apmr.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Extremity Function in Cognitively Healthy Aging, Mild Cognitive Impairment, and Alzheimer's Disease

Abstract: Objective To examine differences in lower-extremity function in cognitive healthy older persons, older persons with mild cognitive impairment (MCI), and older persons with Alzheimer’s disease (AD). Design Descriptive study. Setting University Alzheimer’s disease clinical and research program. Participants Older persons (N=66) were studied (mean age, 76.7y); 22 were cognitively normal, 22 were diagnosed with probable MCI, 22 were diagnosed with probable AD. Interventions Not applicable. Main Outcome M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 41 publications
12
80
1
1
Order By: Relevance
“…This, too, is consistent with other studies, which also did not report any significant slowing in TUG times related to cognitive status [13,36]. Referring to Mirelman et al [13], one could suggest that the gait disturbances related to executive dysfunction are shown in subtasks of gait but do not impair gait speed.…”
Section: Discussionsupporting
confidence: 90%
“…This, too, is consistent with other studies, which also did not report any significant slowing in TUG times related to cognitive status [13,36]. Referring to Mirelman et al [13], one could suggest that the gait disturbances related to executive dysfunction are shown in subtasks of gait but do not impair gait speed.…”
Section: Discussionsupporting
confidence: 90%
“…High CoV values have been related to impaired executive function (Allali et al, 2007). WS is a measure of gait stability and the risk of falls (Abellan van Kan et al, 2009) and has previously been used as a functional measure to assess the presence of MCI (Eggermont et al, 2010;Pettersson et al, 2007). Finally, higher DS values have been related to unsteadiness (Benedetti et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, patients with MCI are at a high risk of developing Alzheimer's dementia (Aggarwal et al, 2006). Besides cognitive decline, MCI patients may manifest early motor and gait dysfunction (Verghese et al, 2008;Eggermont et al, 2010). Gait impairment entails a high risk of falls and institutionalization, as has been shown both in healthy elderly individuals and in patients with dementia (Sheridan and Hausdorff, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The 6-min Astrand Cycle Ergometer test (Monark Ergomedic 839E; Monark Exercise AB, Sweden) estimates the maximal oxygen uptake based on age, body weight and the workload, and average heart rate during the last minute of the test [51]. Functional performance tests include the Timed Up and Go (TUG) test [52], the 30-second chair stand test (the number of full stands in 30 s with arms folded across the chest from a standard chair) [32], the timed 10-min walk test (usual speed) [53] and the timed 400-meter walk test (fast speed) [54]. In addition, dual task performance is measured with the timed 10-min walk test combined with naming the months backwards and counting backwards from 50, respectively [53].…”
Section: Methodsmentioning
confidence: 99%
“…In general, most studies are on nursing home residents with AD and methodological issues restrict the conclusions which may be drawn from these studies [26,27]. In nursing home residents with AD or unspecified dementia, some intervention studies show a positive effect of physical exercise on cognition [28,29], whereas others show no effect [30,31,32]. In home-dwelling patients with AD, cognition has been the primary outcome in only one small study [33], which showed a positive effect of low-intensity physical exercise on tests of global cognition.…”
Section: Introductionmentioning
confidence: 99%